Outcomes of Endoscopic Gluteus Medius Repair: Study of Thirty-four Patients with Minimum Two-Year Follow-up. (19th August 2015) - Chandrasekaran, Sivashankar; Gui, Chengcheng; Hutchinson, Mark R.; Lodhia, Parth; Suarez-Ahedo, Carlos; Domb, Benjamin G.
Abstract : Background: Surgical intervention for partial and full-thickness gluteus medius tears is often recommended for patients who have persistent pain despite nonoperative treatment. Traditionally, the surgical intervention has been carried out through open techniques with good results; however, advantages of endoscopic techniques include less tissue dissection, improved tendon mobilization, and the benefit of arthroscopic correction of intra-articular pathological conditions. The purpose of this report is to provide an update on a previously published study of patients with a gluteus medius tear, with inclusion of additional patients followed for a minimum of two years. Methods: The study included thirty-four patients who had undergone an endoscopic gluteus medius repair with correction of intra-articular pathological conditions between April 2009 and April 2012 and had been followed for a minimum of two years. Patient-reported outcome measures included the modified Harris hip score, Nonarthritic Hip Score, and Hip Outcome Score—Activities of Daily Living and Sport-Specific Subscale. A visual analog scale (VAS) pain score and a patient satisfaction score were also recorded. Results: The cohort consisted of two men and thirty-two women with a mean age of fifty-seven years (range, twenty to seventy-nine years). Ten patients had a full-thickness tear, and twenty-four patients had a partial-thickness tear. Seventeen patients were treated with a suture bridge technique, after completion of the tear if it was not already complete, and seventeen patients were treated with the transtendinous technique. All patients had surgical correction of intra-articular pathological conditions. There was a significant improvement in all four patient-reported outcomes at three specified time-points. The mean VAS pain score decreased from 6.6 preoperatively to 2.4 at the time of the two-year follow-up (p < 0.001). The mean satisfaction score was 8.5 at two years postoperatively. Of twenty-six patients who had a gait deviation preoperatively, fifteen (58%) regained a completely normal gait. There was no significant difference in patient-reported outcome measures between the two surgical techniques. Four patients required total hip replacement at eleven to sixteen months postoperatively. Conclusions: After a minimum of two years of follow-up, endoscopic surgical repair with correction of intra-articular pathological conditions was found to be an effective treatment for patients with a gluteus medius tear. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.